Contextualizing Organic Chemistry through Science–Technology–Society (STS) Pedagogy: Enhancing Conceptual Understanding and Reflective Thinking for Life Sciences Learners - ROSALYN L. BAUTISTA (The Bioscan, 2026)
The increasing demand for scientific literacy and contextualized science instruction has highlighted the need for innovative pedagogical approaches that promote meaningful learning in Organic Chemistry. This study investigated the effectiveness of Science–Technology–Society (STS)-based Organic Chemistry instruction in advancing students' conceptual understanding and reflective thinking within life sciences education. Specifically, it examined students' preconceptions regarding Organic Reactions prior to instruction and the changes in their conceptions following the implementation of an STS-based instructional module. The study employed an action research design guided by W. Edwards Deming's Plan–Do–Study–Act (PDSA) Model, implemented in two iterative cycles involving the design, validation, implementation, and evaluation of an STS- based learning module. Participants were ten first-year Bachelor of Science in Fisheries and Aquaculture Sciences (BFAS) students enrolled in Organic Chemistry at Isabela State University– Roxas Campus during the second semester of School Year 2018–2019. Data were collected using a researcher-developed 20-item Concept Test, the Students' Perceptions of Science Class Questionnaire, the Questionnaire to Measure the Level of Reflective Thinking, and the Attitudes toward the Use of STS-Based Activities Questionnaire. Descriptive statistics and the Wilcoxon Signed-Rank Test were employed to analyze students' conceptual understanding before and after the intervention. Findings revealed that students initially possessed limited conceptual understanding and several misconceptions concerning Organic Reactions. Following the implementation of the STS-based instructional module, students demonstrated substantial conceptual improvement, as evidenced by an increase in the mean concept test score from 8.60 to 12.90 and a statistically significant difference between pretest and posttest scores (Z = –2.818, p = .005). The intervention effectively facilitated conceptual change by enabling students to reconstruct prior knowledge through contextualized, inquiry-oriented, and learner-centered learning experiences. The findings suggest that integrating the Science–Technology–Society (STS) instructional approach into Organic Chemistry instruction significantly enhances conceptual understanding and reflective thinking while promoting scientific literacy among life sciences students. The study recommends the wider adoption of STS-based pedagogical approaches in higher education science curricula to foster meaningful learning and develop scientifically literate graduates capable of applying chemical concepts to real-world biological, environmental, and societal contexts.